New optical and radiocarbon dates from Ngarrabullgan Cave, a Pleistocene archaeological site in Australia : implications for the comparability of time clocks and for the human colonization of Australia - David, Bruno; Roberts, Richard; Tuniz, Claudio; Jones, Rhys; Head, John
The human settlement of Australia falls into that period where dating is hard because it is near or beyond the reliable limit of radiocarbon study; instead a range of luminescence methods are being turned to (such as thermoluminescence at Jinmium: December 1996 ANTIQUITY). Ngarrabullgan Cave, a rock-shelter in Queensland, now offers a good suite of radiocarbon determinations which match well a pair of optically stimulated luminescence (OSL) dates Ñ encouraging sign that OSL determinations can be relied on.